Prevalence of folic acid supplement consumption before and during pregnancy, and its determinants among community health center referrals - Neda Ezzeddin; Rosa Zavoshy; Mostafa Noroozi (Korean Society of Obstetrics and Gynecology, 2019)
ObjectiveThe aim of this study is to assess the prevalence and determinants of folic acid supplementation among women referred to community health centers.MethodsThis was a cross-sectional study conducted in 325 women referred to community health centers. The subjects were selected from 8 community health centers, using a stratified sampling technique. Data regarding demographics, socioeconomic status, obstetrics, folic acid supplementation status, and household food security status were obtained via questionnaires. The data was analyzed in SPSS v22.ResultsThe prevalence of folic acid supplementation both before and during pregnancy was 54.5%. The results of the study showed that folic acid supplementation had a significant positive association with education level (odds ratio [OR],0 .441; 95% confidence interval [CI], 0.199-0.977; P<0.05), being employed (OR, 0.353; 95% CI, 0.148-0.840; P<0.05), and planned pregnancy (OR, 18.113; 95% CI, 7.371-44.51; P<0.001). However, other variables, including age, husband's age, husband's education and employment status, the number of prior pregnancies, economic satisfaction, and household food security, were nonsignificant factors affecting folic acid supplementation.ConclusionWomen with lower socioeconomic status are less likely to take folic acid supplements, and more effort should be made to increase their awareness of the importance of supplementation. Unplanned pregnancy is another strong risk factor for not supplementing with folic acid, and thus should be avoided.